Understanding the role of genetic susceptibility (ACE2 and TMPRSS2) in COVID-19. Issue 1 (31st December 2022) - Aborode, Abdullahi Tunde; Onigbinde, Sherifdeen Bamidele; Sanusi, Khadijah Omoshalewa; Alaba, Noah; Rasaq-Lawal, Aderinola H.; Obadawo, Babatunde Samuel; Olatoyosi, Allison; Adeniran-Obey, Saidat Omowunmi; Onwukwe, Victor; Asogwa, Uchenna; Arinola, Ridwan Iyanu; Imani, Seun Idowu; et al.
ABSTRACT: COVID-19-related morbidity and mortality are significantly increased with increasing age and the presence of co-existing health conditions, such as cancer and cardiovascular disease. While most infected people recover, even very young and otherwise healthy patients may unpredictably succumb to this disease. COVID-19 is highly susceptible to Angiotensin-converting enzyme 2 (ACE2) and Transmembrane protease-serine 2 (TMPRSS2) polymorphisms altering the angiotensinogen-ACE2 interactions, such as p. Arg514Gly and its prevalence. The article describes the role of understanding the genetic basis of COVID-19 and its susceptibility to human genes.